Transparent Messenger - Hermit III Plasy 1994 : Symposium. - Beckett, Samuel; Calvino, Italo; Poe, Edgar Alan; Swift, Jonathan; Wilkins, John (Plasy : Hermit Foundation - Plasy Monastery, 1994)
Theis, Bert ; Tropisme, Stichting ; Czergö, Attila ; Trabant, Tomasz Matuszak ; Mrozowitz, Jacek ; Haselden, Ron ; Bouzek, Michal ; Kivland, Sharon ; Delia, Michel ; Signer, Roman ; Kordecki, Lorraine ; Klimczak, Adam ; Kubinský, Monika & Bohus ; Bakal, Boris ; Chander, Jagdish ; Elsen, Trudi Van Der ; Dukic, Sandro ; Powell, Richard ; Panhuysen, Paul ; Brand, Jens ; Riedl, Waldo ; Hirt, Erhard ; Klapper, Martin ; Davies, Hugh ; Groeneveld, Martien ; Fajt, Pavel ; ReRun, Stichting ; Silver ; Machazjdik, Peter ; Piacek, Marek ; Florian ; Cusack, Peter ; Rova Saxophone Quartet ; Nikl, Petr ; Sejn, Milos ; Mazur, Anchelka ; Meneses, James ; Fulkerson, James ; Anderson, John ; Mehta, Rajesh ; Janota, Oldrich ; Kafka, Ivan ; Moser-Wagner, Gertrude ; Seebach, An
Speciale kast
Engels
boek